Analysis of Focus Difficulties in Student with ADHD-Like Characteristics During the Learning Process - Yanah Yanah; Lusiana Suciati Dewi (Jurnal Pendidikan dan Sastra Inggris, 2026)
This research aimed to analyze focus difficulties faced by an early chilhood student with ADHD-like characteristics during the learning process. This study used a qualitative case study approach. The subject of this research was one preschool student who showed behaviors similar to attention deficit hyperactivity disorder (ADHD) but had never received a medical diagnosis. Data collection techniques include observation, interviews, and documentation. Interviews were conducted with the classroom teacher and student at the PAUD school. The results showed that the student experienced difficulty maintaining attention during learning activities, was easily distracted by external triggers, frequently left the seat during class activities. The student also tended to lose concentration when listening to teacher explanations and preferred learning activities involving movement and visual media. These conditions influenced the student’s participation during the learning process. The finding indicate that children with ADHD-like characteristics require appropriate instructional strategies and teacher support to enhance focus during classroom learning. To optimize student concentration during class hours, the implementation of dynamic and compelling instructional approaches by teacher is necessitated by these outcomes.